Uji Kualitatif Fitokimia Ekstrak Daun Alpukat (Persea americana Mill.) dan Daun Belimbing Wuluh (Averrhoa bilimbi L.) serta Kombinasinya - Azizah Lailatul Nadhifah; Melindra Mulia (Lembaga Yasin AlSys, 2025)
Plants are an important source of natural medicinal compounds, particularly through secondary metabolites with biological activity. Avocado leaves (Persea americana) and belimbing wuluh leaves (Averrhoa bilimbi) are known to contain such compounds and hold potential as natural medicines. This study aims to identify the secondary metabolite content in combined extracts of avocado and belimbing wuluh leaves through phytochemical testing. The method used was qualitative phytochemical analysis to detect the presence of active compounds in each extract and in their combination. The results show that avocado leaf extract contains flavonoids, phenols, alkaloids, saponins, and steroids, while belimbing wuluh leaf extract contains phenols, flavonoids, alkaloids, and steroids but lacks saponins. After combining the two extracts, the test results indicated the presence of flavonoids and phenols. These findings suggest that the combined extracts retain key bioactive compounds with potential pharmacological effects. The study concludes that the combination of avocado and belimbing wuluh leaf extracts contains secondary metabolites that may be further developed as natural medicinal ingredients. The implications open opportunities for future research to examine the pharmacological activity and therapeutic potential of this plant extract combination.